Arithmetic properties of ℓ-regular partitions - Cui, Su-Ping; Gu, Nancy S.S. (Advances in applied mathematics, 2013)
For a given prime p, by studying p-dissection identities for Ramanujanʼs theta functions ψ(q) and f(−q), we derive infinite families of congruences modulo 2 for some ℓ-regular partition functions, where ℓ=2,4,5,8,13,16.